Development and validation of scales for attitudes, self-reported practices, difficulties and knowledge among home care nurses providing palliative care. (June 2016) - Shimizu, Megumi; Nishimura, Misako; Ishii, Yoko; Kuramochi, Masayo; Kakuta, Naoe; Miyashita, Mitsunori
Abstract: Purpose: Although educational programs for nurses are required to ensure high-quality home care, there is currently no scale to appropriately evaluate such programs for home care nurses providing palliative care. We developed and validated four scales to evaluate home care nurses' attitude, self-reported practices, difficulties, and knowledge regarding home palliative cancer care, and identified factors associated with home care nurses' attitude, self-reported practices, and difficulties. Method: The scale items were generated based on literature review and a cross-sectional questionnaire survey was conducted. Experienced home care nurses from visiting nurse stations who enrolled in a home palliative care educational program were recruited for this survey. Results: Of the 125 questionnaires delivered to home care nurses, 122 were returned (response rate, 98%). After factor analysis, the scale for attitude comprised four domains with 12 items, the scale for self-reported practices comprised six domains with 26 items, and the scale for difficulties comprised five domains with 18 items. Cronbach's alphas for these scales were 0.61–0.70. After using the Item Response Theory model, the scale for knowledge was found to comprise 26 items. The multiple logistic regression model showed that experience in caring for terminal patients at home or in hospitals were associated with having more positive attitude, higher self-reported practices and lower difficulties. Conclusions: We developed valid and reliable scales to evaluate home care nurses' attitude, self-reported practices, difficulties, and knowledge regarding home palliative cancer care. These scales potentially useful for evaluating a home palliative cancer care education program for nurses. Highlights: We developed four scales evaluating nurses regarding home palliative cancer care. The scales evaluate home care nurses' attitudes, practices, difficulties, and knowledge. These scales can be used to assess the individual needs of home care nurses.